Effects of apple cider vinegar on glycaemic control, lipid profile, and anthropometric outcomes in adults: A systematic review of randomized controlled trials. - Panda, Dr. Suvendu Kumar; Gouda , Surya Narayan; Mishra, Pratyush; Panigrahy, Srikanta (Student’s Journal of Health Research Africa, 2026)
Background: Apple cider vinegar (ACV) is widely used as a complementary dietary intervention for improving metabolic health, yet clinical evidence regarding its efficacy remains inconsistent. Objectives: To systematically review randomized controlled trials (RCTs evaluating the effects of apple cider vinegar on anthropometric measures, glycaemic control, lipid profile, and related metabolic outcomes in adults. Methods: This systematic review followed PRISMA 2020 guidelines. PubMed/MEDLINE, Scopus, Web of Science, CENTRAL, and Google Scholar were searched from inception to January 2025. Randomized or controlled clinical trials in adults (≥18 years) evaluating oral apple cider vinegar as a standalone intervention for at least two weeks were included. Two reviewers independently performed study selection, data extraction, and quality assessment. Risk of bias was assessed using the Cochrane RoB-2 tool. Eleven RCTs were included, with overall risk of bias ranging from low to high; inadequate blinding was the most frequent limitation. The protocol was not prospectively registered, and findings were synthesized narratively. Results: Eleven randomized controlled trials involving over 750 participants were included. Most studies enrolled individuals with type 2 diabetes mellitus, overweight/obesity, or dyslipidaemia. ACV supplementation (15–30 mL/day for 4–12 weeks) consistently reduced fasting blood glucose and produced modest improvements in HbA1c among diabetic participants. Significant reductions in triglycerides and total cholesterol were observed in dyslipidaemic populations, while effects on LDL-C and HDL-C were variable. Modest but significant reductions in body weight, body mass index, and waist circumference were reported, particularly in overweight or obese individuals. ACV was generally well tolerated, with only mild gastrointestinal adverse effects. Conclusions: Apple cider vinegar supplementation provides modest but clinically relevant improvements in glycaemic control, lipid parameters, and anthropometric outcomes, particularly in individuals with metabolic disorders. ACV may serve as a safe adjunctive dietary intervention; however, larger and longer-term trials are required to confirm sustained benefits.